Co-creating Relationship Repair: Pathways to Reconstructing Destabilized Organizational Identification - Petriglieri, Jennifer Louise (Administrative science quarterly, 2015)
Through a qualitative study of BP executives during and after the 2010 Gulf of Mexico oil rig explosion and spill, I examine whether and how the relationship between an organization and its members can be repaired once damaged. I found that the incident destabilized executives' organizational identification, leading them to doubt the alignment between their own identity and BP's, and generated feelings of ambivalence toward the organization and their role in it. This marked the onset of a process through which members reassessed their identification, leading them either to reidentify and repair their relationship with BP or to deidentify and sever that relationship. Executives resolved their ambivalence and strongly reidentified only when they had organizationally sanctioned opportunities, through working on BPs' response to the incident, to enact the identity attributes of technical excellence and environmental consciousness that were threatened by the Gulf events, suggesting that full relationship repair requires active co-creation by the member and the organization. Absent co-created repair, social information that supported or undermined executives' identification with BP was key to resolving ambivalence and destabilized identification. Building on these findings, I develop a model of repairing damaged relationships after a transgression, with the concepts of destabilized identification and co-created repair, and the mechanism of ambivalence resolution at its center.